Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0110-001 Secretary's. HVT/FC/456. GR/MLA. Mr. G. Reed, 27th April, 1939. The National Union of Seamen, St. George's Hall, Westminster Bridge Road, S.E.1. Dear Mr. Reed, SPANISH SEAMEN. Further to my telephone conversation with you in connection with your letter of the 21st instant I note the opinion of your Executive in regard to the possibility of Spanish seamen being drafted to British ships, and also the desire of your Executive to cease administering the fund on our behalf as from April 29th. In accordance with our telephone conversation we should be very grateful if, pending further arrangements, you would agree to continue for a maximum of two weeks the administration of the fund. If you will be so good as to let us have the receipts for all the money paid up to and including April 29th we will immediately reimburse you. If, accompanying these accounts, or at a later stage, we can secure a list of the men and their desires in regard to emigration, that will be very helpful. Your assistance in all these matters is very greatly appreciated. Yours sincerely, Assistant Secretary. 292/946/25a/110